The Influence of Financial Literacy and Financial Technology on Member Loyalty in the Ikhlas Cooperative, Cilacap - Wiwit Ary Nugroho (Yayasan Payungi Smart Madani, 2025)
This research aims to analyse the influence of financial literacy and the use of financial technology on cooperative members’ loyalty, with a particular focus on KKPRI Ikhlas Cilacap as a case study.The research method employs a quantitative approach through a survey of 300 respondents selected by purposive sampling from a total of 600 active cooperative members, using a four-point Likert scale questionnaire that has been tested for validity and reliability. Data analysis was carried out through classical assumption testing, multiple linear regression, as well as F-tests and t-tests to examine both simultaneous and partial effects. The findings reveal that financial literacy has a significantly positive impact on members’ loyalty by enhancing their ability to make rational financial decisions, while the adoption of fintech has a tangible effect on improving efficiency, transparency, and members’ trust. Further discussion confirms that the combination of sound financial literacy and appropriate fintech implementation can sustainably strengthen members’ loyalty, in line with the theoretical framework adopted. These findings contribute academically by enriching the literature on cooperative management in the digital era and provide practical recommendations for cooperative boards to enhance financial literacy education and optimise service digitalisation as a strategy to sustain member loyalty.